DIGITAL MARKETING STRATEGY: THE ROLE OF E-WOM IN MEDIATING THE CONSUMER BUYING DECISION PROCESS AMONG INSTAGRAM FOLLOWERS OF FOOD SECTOR MSMES IN MUARA BUNGO - Hidayat, Husnil; Susanto, Perengki; Patrisia, Dina (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyse the influence of social media marketing and content marketing on the consumer buying decision process, with electronic word of mouth (e-WOM) as a mediating variable among followers of food sector MSMEs on Instagram in Muara Bungo. Method: This study employs a survey-based approach and is a quantitative associative study with an explanatory research approach. The population in this study consists of Instagram followers of SMEs in the food sector in Muara Bungo who are interested in making online purchasing decisions for food snacks sold through Instagram accounts, with a sample size of 130 individuals. Data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM). Results: Based on the research findings, it was concluded that social media marketing has a positive and significant effect on the consumer buying decision process. Content marketing has a positive effect but is not significantly related to the consumer buying decision process. Social media marketing has a positive and significant effect on electronic word of mouth. Content marketing has a positive and significant effect on electronic word of mouth. Electronic word of mouth has a positive and significant effect on the consumer buying decision process. Novelty: Electronic word of mouth acts as a mediating variable between the effect of social media marketing on the consumer buying decision process, with the form of mediation being complementary mediation in the form of partial mediation. Electronic word of mouth also acts as a mediating variable between the influence of content marketing on the consumer buying decision process, with the form of mediation being indirect-only mediation, which is a form of full mediation.